Hubungan Kegiatan Muhadhoroh Santri Terhadap Keterampilan Komunikasi di Pondok Pesantren Modern Ar-Ridho Sentul - Farhanul Hakim; Maemunah Sa’diyah (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research is about how the relationship of muhadhoroh activities of students to communication skills. This research was conducted at Ar-Ridho Sentul Modern Islamic Boarding School. The problem of this research is how muhadhoroh activities on students, how communication skills on students and how is the relationship between muhadhoroh activities on communication skills. The purpose of this study was to determine how muhadhoroh activities on students, how communication skills on students and how the relationship between muhadhoroh activities on communication skills. The method used is quantitative descriptive, the data collected is obtained from the results of the questionnaire, the results of the study state that: The relationship of muhadhoroh activities of students to communication skills is 53.3%. The results of these calculations through the determination test analysis (KD) = r2 x 100% or 0.533 x 100% = 53.3%. In addition, in the calculation results through the significance test analysis Fcount (60.439) > Ftable (3.175) with Sig. (0.002) < ɑ (0.05), then Ho is rejected and Ha is accepted. Keywords: Muhadhoroh Activities; Communication Skills